Pendekatan Layanan Pendidikan Untuk Anak Berkebutuhan Khusus - Lestari, Thiara Deah (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This study aims to explore an effective educational service approach for children with special needs through the Systematic Literature Review (SLR) method. This method is used to identify, disseminate, and interpret all research relevant to the topic being studied. The focus of the study includes three main elements: an inclusive approach, the use of educational technology, and collaboration between parents, teachers, and other professionals. The results of the literature review indicate that an inclusive approach allows children with special needs (ABK) to learn in a supportive environment, which can improve their social engagement and academic achievement. The use of educational technology, such as special software and communication aids, has been shown to be effective in overcoming learning barriers and improving children's cognitive and motor skills. In addition, close collaboration between parents, teachers, and other professionals is essential in designing and implementing a comprehensive and consistent individual education plan (IEP). This study concludes that an integrated and inclusive educational service approach can provide the best opportunity for children with special needs to reach their full potential in a supportive and adaptive environment.